Pista centrifuga - Scuderi, G.
It is a circular track of varying reducing sizes with changeable incline. It uses the centrifugal force to allow the runner to maintain the speed and stance of natural way of running even if running in a small space. It can be used by more than one person (the smallest model can accommodate 6 runners at the same time). It simulates a hiking trail with an increasing sense of gravity, therefore it will create a potential muscular development with the allows the individual to develop at the maximum the body mechanic power during the races in running stance. It is recommended for professional runners but it can also be easily used by those who like to run and want to keep fit. It has been found that the track circular design attracts children introducing them to a new form of play and exercise during the formative years. It improves flexibility, reaction time, muscular strenght and coordination (not using weights during the child formative years of development) useful as well as for adults physical maintenance and weight less. It can be placed either indoor o outdoor forum, if located inside a gym can represent a decorative element.